Quantum Singularities in (2+1) Dimensional Matter Coupled Black Hole Spacetimes - Ünver, Özlem (Eastern Mediterranean University (EMU), 2012)
ABSTRACT: Quantum singularities are considered in matter coupled 2+1 dimensional spacetimes in Einstein’s theory. The occurrence of naked singularities in the spacetimes both in linear and non-linear electrodynamics in Einstein-Maxwell as well as in the Einstein-Maxwell-Dilaton gravity and pure magnetic Einstein-Power-Maxwell theory are considered. It is shown that the inclusion of the matter fields changes the geometry. The classical central singularity at turns out to be quantum mechanically singular for quantum particles obeying Klein-Gordon equation but nonsingular for fermions obeying Dirac equation in all space times except the class of static pure magnetic spacetime. The physical properties of the 2+1 dimensional magnetically charged solutions in Einstein-Power-Maxwell theory with particular power of the Maxwell field are investigated. The true timelike naked curvature singularity develops when which constitutes one of the striking effects of the power Maxwell field. For specific power parameter, the occurrence of timelike naked singularity is analysed in quantum mechanical point of view. It is shown that the class of static pure magnetic spacetime in the power Maxwell theory is quantum mechanically singular when it is probed with fields obeying Klein-Gordon and Dirac equations in the generic case. Keywords: Quantum singularity, naked singularity, 2+1 dimensional spacetimes. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Einstein teorisi içinde, kuvantum tekillikleri madde eklenmiş 2+1 boyutlu uzay-zamanlarda çalışılmıştır. Çıplak tekilliklerin oluşumu doğrusal ve doğrusal olmayan elektrodinamik Einstein-Maxwell, hem de Einstein-Maxwell-Dilaton ve manyetik Einstein-Üslü-Maxwell teorilerinde incelenmiştir. Madde alanlarının eklenmesiyle geometrinin değiştiği gösterilmiştir. Statik manyetik uzay-zaman haricindeki tüm çalışılan uzay-zamanlarda noktasındaki klasik merkezi tekilliğin Klein-Gordon denklemine uyan parçacıklar için kuvantum tekil kaldığı fakat Dirac denklemine uyan fermionlar için bu tekilliğin ortadan kalktığı görülmüştür. Einstein-Üslü-Maxwell teorisinde 2+1 boyutlu manyetik yüklü çözümlerin fiziksel özellikleri özel k kuvvetiyle incelenmiştir. değerleri için zamansal, çıplak, eğrilik tekilliğinin oluştuğu görülmüştür ki bu durum üslü Maxwell alanının en büyük etkisidir. Belli bir k değeri için kuvantum mekaniksel açıdan zamansal çıplak tekilliğin oluşumu incelenmiştir. Üslü Maxwell teorisindeki statik manyetik uzay-zamanın Klein-Gordon ve Dirac alanları içerisinde incelendiğinde, kuvatum mekaniksel olarak tekil kaldığı gösterilmiştir. Anahtar Kelimeler: Kuvantum tekillik, çıplak tekillik, 2+1 boyutlu uzay-zamanlar.
Doctor of Philosophy in Physics. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Physics, 2012. Supervisor: Prof. Dr. Özay Gürtuğ.
Keywords: Physics; Space and Time; Quantum Singularity - Naked Singularity - 2 1Dimensional Spacetimes